The Correct Way to Use Technology in the Early Childhood Classroom (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2023)
Technology use in the education setting is an ongoing controversy and there are mixed reviews on its positivity and negativity of exposure and use in early childhood classrooms. Because technology is prevalent in society today, exposure at young ages is important for children to succeed. Instead of asking if technology should be used in early childhood classrooms, we should model the correct way to use it there. The use of technology in the early childhood classroom should include tools and experiences used to prepare students for formal classroom instruction and the development of their different domains of learning. It will additionally help facilitate scaffolding and extension of learning while supporting connections between school and home.            Keyword: DATU
Keywords: DATU